2021
DOI: 10.1088/1361-6528/ac378b
|View full text |Cite
|
Sign up to set email alerts
|

X-ray high frequency pulse emission characteristic and application of CNT cold cathode x-ray source cathode x-ray source

Abstract: Carbon nanotube (CNT) field-emission x-ray source has great potential in x-ray communication (XCOM) because of its controllable emission and instantaneous response. A novel voltage loading mode was proposed in this work to achieve high-frequency pulse x-ray emission. The characteristics of cathode current and pulse x-ray versus voltage, frequency, and pulse amplitude were studied, and XCOM data transmission experiment was carried out. Results showed that the CNT cold cathode x-ray source, as a communication si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These studies built a solid foundation for XCOM development. In addition, Tang et al conducted a series of studies regarding XCOM, including the penetrative properties of X-rays [14], X-ray high frequency pulse emission characteristics [15], and collimating/ focusing optical systems [16]. The potential applications of XCOM in the Mars scenario [3,17] and during Earth reentry [18][19][20] were also studied.…”
Section: X-ray Communication (Xcom) Is a Revolutionary Technique In S...mentioning
confidence: 99%
“…These studies built a solid foundation for XCOM development. In addition, Tang et al conducted a series of studies regarding XCOM, including the penetrative properties of X-rays [14], X-ray high frequency pulse emission characteristics [15], and collimating/ focusing optical systems [16]. The potential applications of XCOM in the Mars scenario [3,17] and during Earth reentry [18][19][20] were also studied.…”
Section: X-ray Communication (Xcom) Is a Revolutionary Technique In S...mentioning
confidence: 99%
“…So far, the temporal responses of several kinds of quasi-one-dimensional field emitters have been reported. It is found that the response time of CNT can be down to ~100 ns [19,20], while that for individual SiC nanowire is ~1 ms [21]. For ZnO nanowire, the response time is tens of microseconds in a MOSFET controlled device [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can be miniaturized via modern micro-fabrication techniques. All these advantages make it promising in the realization of a high-performance vacuum electron source [1][2][3][4][5][6] as well as other novel applications such as flat panel field emission display [7][8][9], parallel electron beam lithography [10,11] and flat panel X-ray source [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%